Customer participation enhancement through empowerment and engagement: a study in higher education - Boaventura, Patricia Silva Monteiro (2019)
This dissertation, presented in the format of three articles, has the general goal to explore how value co-creation can be promoted in the context of highly relational services. Concepts such as customer engagement, participation and empowerment have become more frequent in the literature discussing value co-creation, but not without overlaps and misunderstandings among their definitions and relationships. The first article presents a literature review on consumer participation, which is a topic that is not recent but whose investigation perspective has been changed. Older studies on customer participation focused on understanding how consumers contribute to organizations’ productivity increases. More recently, the concept has been investigated as a mechanism for more active customer interaction – voluntary participation – during exchanges. The study explored psychological empowerment as an antecedent of voluntary participation and proposed that this relationship follows an inverted-U curve shape. The second and third articles explore the context of higher education, which is a highly relational service. The second article reports on a study that adopted a mixed-method approach, using in-depth interviews, observations and a survey to explore the relationships among perceived empowerment, psychological engagement and voluntary participation in the context of the classroom. It shows that engagement fully mediates the effect of empowerment on students’ voluntary participation. The third article analyzes data collected from in-depth interviews and observations of traditional classrooms and new initiatives adopted at two business schools. The article explores how institutional arrangements may restrain the effect of perceived empowerment on engagement. It identifies that norms and shared beliefs restrain this effect. This also allows us to conclude that successful initiatives are able to adopt particular norms and beliefs, fostering an environment of trust and consequently promoting greater student engagement. Additionally, it explores how engagement with a discipline affects the relationship between students and the overall learning experience. This dissertation advances the knowledge on how empowerment, engagement and participation are related and how they can promote greater value co-creation, and its results could be of great value to higher education managers and other highly relational service managers.